2004
DOI: 10.1007/s10330-004-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Fentanyl for Management of Cancer Pain in Elderly Patients in China

Abstract: Objective: To assess the effect and adverse effects of transdermal fentanyl for elderly patients with cancer pain in China. Methods: A total of 1664 elderly patients (aged 65-90 with mean age of 72.6) with cancer pain enrolled in the multicenter study from 136 institutes in China. Of them, 408 (28.8%) patients were 75 years old or older. All patients received transdermal fentanyl for the management of cancer pain. The patients were asked to record the attacks of pain, quality of life, and any side effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Yu ve ark. [13] da yapmış oldukları çalışmada, 65 yaşının üstündeki 1664 kronik kanser hastasında TDF kullanmışlar ve ağrı şiddetinde %97'nin üstünde azalma saptamışlardır. Uygun analjezik ajan seçiminin yanında, hastalarımızı kısa aralıklar ile kontrole çağırmamızın da ağrı kontrolündeki başarımızı etkileyen önemli bir etken olduğunu düşünmekteyiz.…”
Section: Discussionunclassified
“…Yu ve ark. [13] da yapmış oldukları çalışmada, 65 yaşının üstündeki 1664 kronik kanser hastasında TDF kullanmışlar ve ağrı şiddetinde %97'nin üstünde azalma saptamışlardır. Uygun analjezik ajan seçiminin yanında, hastalarımızı kısa aralıklar ile kontrole çağırmamızın da ağrı kontrolündeki başarımızı etkileyen önemli bir etken olduğunu düşünmekteyiz.…”
Section: Discussionunclassified
“…Oral morphine is generally accepted to be the drug of choice for maintenance therapy of moderate-severe cancer pain. But transdermal fentanyl is challenging the position because of its convenience, relative lower incidence of constipation and higher compliance of patients reported in clinical trials [ 42 - 44 ]. Clark et al and Tassinari et al in three meta-analyses reported two drugs were equally effective in improving the score of pain with less adverse effects for transdermal fentanyl [ 4 - 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…One open multicenter study from China 143 investigated the management of moderate to severe cancer pain in 1664 elderly patients aged 65 to 90 years with transdermal fentanyl 25 to 150 μg/hour initially to 25 to 200 μg/hour at days 15 and 30. Transdermal fentanyl was effective in reducing pain in >97% of patients and improving quality of life rate from 25% to >71%.…”
mentioning
confidence: 99%